FROM ENGAGEMENT TO LOYALTY: A STRUCTURAL EQUATION MODELLING APPROACH IN THE HARYANA BANKING INDUSTRY - Dr. Kanchan Rani; Ramandeep Kaur (IJRDO - Journal of Applied Management Science, 2025)
Purpose: This study examines the antecedents of employee engagement and its subsequent impact on organizational commitment and employee retention within the Indian banking sector, specifically in Haryana. The research investigates the roles of leadership, perceived organizational support, psychological capital, and value congruence in shaping employee engagement. Design/methodology/approach: A quantitative research design was adopted, utilizing data from 400 banking professionals across four major public and private sector banks. Validated measurement scales were employed, and the data were analyzed using confirmatory factor analysis (CFA) and structural equation modeling (SEM) via SPSS-AMOS. Findings: Results indicate that perceived organizational support, psychological capital, and value congruence significantly and positively influence employee engagement, with psychological capital emerging as the strongest predictor. Leadership, however, did not exhibit a significant direct effect on engagement in this context. Engagement, in turn, significantly enhanced organizational commitment and employee retention. The measurement model demonstrated strong reliability, convergent and discriminant validity, and excellent model fit (CFI = 0.962, RMSEA = 0.028). Practical implications: The findings suggest that banking institutions should invest in fostering supportive organizational climates, enhancing employees’ psychological capital, and aligning organizational values with those of employees to strengthen engagement. This can lead to higher commitment and reduced turnover rates. Originality/value: This study extends the literature on engagement in emerging economy contexts, providing empirical evidence that, in the Indian banking sector, organizational and psychological resources may outweigh direct leadership effects in driving engagement. It offers actionable insights for human resource strategy in knowledge-intensive service industries.